2011
DOI: 10.1002/dys.437
|View full text |Cite
|
Sign up to set email alerts
|

Parental Literacy Predicts Children's Literacy: A Longitudinal Family‐Risk Study

Abstract: This family-risk (FR) study examined whether the literacy skills of parents with dyslexia are predictive of the literacy skills of their offspring. We report data from 31 child-parent dyads where both had dyslexia (FR-D) and 68 dyads where the child did not have dyslexia (FR-ND).Findings supported the differences in liability of FR children with and without dyslexia: the parents of the FR-D children had more severe difficulties in pseudoword-reading and spelling accuracy, in rapid word recognition, and in text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 42 publications
6
47
0
4
Order By: Relevance
“…show that parental rapid naming is predictive of their offspring's naming and reading fluency (Torppa et al, 2011;van Bergen et al, 2014b). It thus supports the notion that parental skills are informative of their offspring's liability for dyslexia (van Bergen et al, 2014b).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…show that parental rapid naming is predictive of their offspring's naming and reading fluency (Torppa et al, 2011;van Bergen et al, 2014b). It thus supports the notion that parental skills are informative of their offspring's liability for dyslexia (van Bergen et al, 2014b).…”
Section: Discussionsupporting
confidence: 71%
“…The risk for dyslexia has been reported to range from fourfold (Puolakanaho, et al, 2007) to tenfold (van Bergen, de Jong, Plakas, Maassen, & van der Leij, 2012) for children with family risk compared to children without such risk. Family risk has predicted children's reading development over and above children's skills in the key cognitive precursors, such as phonological awareness, rapid naming, and letter knowledge (Puolakanaho et al, 2007;Torppa, Eklund, van Bergen, & Lyytinen, 2011). Furthermore, studies predicting children's skills with parent's skills have suggested that specific parental skills may be informative in assessing children's liability for dyslexia beyond their own cognitive development (Torppa et al, 2011;van Bergen et al, 2014a).…”
Section: Late-emerging and Resolving Dyslexia: A Follow-up Study Frommentioning
confidence: 99%
“…Despite the substantial impact of children's underlying skills on reading, parental skills explained additional variance (previously also found by Torppa et al, 2011;van Bergen et al, 2012;in family-risk studies). In fact, half of parents' effects bypassed and half operated through children's underlying skills.…”
Section: Discussionmentioning
confidence: 59%
“…A Dutch and a Finnish familial risk study showed a moderate correlation between parents' and children's reading fluency (Torppa, Eklund, van Bergen, & Lyytinen, 2011;van Bergen, de Jong, Plakas, Maassen, & van der Leij, 2012). A recent Dutch family study (based on an unselected sample) reported a parent-offspring correlation for reading fluency of .35 (van Bergen, Bishop, van Zuijen, & de Jong, 2015).…”
Section: Introductionmentioning
confidence: 95%